The Role of Astrocyte Dysfunction in Parkinson's Disease Pathogenesis. Issue 6 (June 2017) - Booth, Heather D.E.; Hirst, Warren D.; Wade-Martins, Richard
Abstract : Astrocytes are the most populous glial subtype and are critical for brain function. Despite this, historically there have been few studies into the role that they may have in neurodegenerative diseases, such as Parkinson's disease (PD). Recently, however, several studies have determined that genes known to have a causative role in the development of PD are expressed in astrocytes and have important roles in astrocyte function. Here, we review these recent developments and discuss their impact on our understanding of the pathophysiology of PD, and the implications that this might have for its treatment. Trends: PD is characterised by the degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNc). Neuroinflammation in the SNc is a consistent feature of PD. Recent studies of eight proteins implicated in PD demonstrate that they have functional roles in astrocyte biology. These studies provide evidence that PD may develop, at least in part, due to astrocyte dysfunction.